The Dynamics of Collaborative Picture Sequencing in Arabic Language Learning Through The Integration of Lev Vygotsky’s Theory - Sovia Fahraini; Muzakki Abdurrahman; Muhammad Thohir; Moh Sholeh Afyuddin (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2025)
Arabic as a foreign language has high complexity, especially in writing skills, so it requires innovative learning strategies. Collaborative Picture Sequencing based on images and cooperation, with Vygotsky's theory, is effective in improving writing skills, motivation, and cooperation, although it requires attention to member dominance and time. Based on this context, this study aims to understand the dynamics of Collaborative Picture Sequencing in Arabic language writing learning, especially through the integration of Vygotsky's collaboration theory, so that the strategy can be implemented effectively according to students' learning needs. This study uses a descriptive-analytical qualitative method, with data from observations, interviews, and documentation of writing results before and after the implementation of the strategy. The results of the study show four main findings: [1] Ease of Expressing Ideas through Sequential Images. [2] Dynamics of Collaboration in Language Exchange, [3] Scaffolding in the Zone of Proximal Development, [4] Improving the Quality of Written Products. By understanding these dynamics, teachers are expected to be able to design more effective and contextual writing learning, increase students' motivation and writing skills, as well as become a reference for developing collaboration-based materials so that each student develops according to their potential.